2018
DOI: 10.3390/rs10091422
|View full text |Cite
|
Sign up to set email alerts
|

Forest Variable Estimation Using a High Altitude Single Photon Lidar System

Abstract: As part of the digitalization of the forest planning process, 3D remote sensing data is an important data source. However, the demand for more detailed information with high temporal resolution and yet still being cost efficient is a challenging combination for the systems used today. A new lidar technology based on single photon counting has the possibility to meet these needs. The aim of this paper is to evaluate the new single photon lidar sensor Leica SPL100 for area-based forest variable estimations. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
2
14
1
Order By: Relevance
“…The advent of new ALS technologies such as single photon lidar may enable cost-effective landscape-level characterization of the ground surface with sufficient accuracy to support DAP normalization. Single photon systems have the ability to fly at greater elevations and faster speeds, acquiring ALS data for less cost than currently standard systems [140]. This raises the potential for DAP data to be used to support forest inventory frameworks, especially areas beyond existing EFI boundaries.…”
Section: Acquisition Planningmentioning
confidence: 99%
“…The advent of new ALS technologies such as single photon lidar may enable cost-effective landscape-level characterization of the ground surface with sufficient accuracy to support DAP normalization. Single photon systems have the ability to fly at greater elevations and faster speeds, acquiring ALS data for less cost than currently standard systems [140]. This raises the potential for DAP data to be used to support forest inventory frameworks, especially areas beyond existing EFI boundaries.…”
Section: Acquisition Planningmentioning
confidence: 99%
“…biomass and volume) and the metrics extracted from LiDAR data. Airborne laser scanning (ALS) is the consolidated technique to retrieve tree or stand parameters and to detect forest changes using multitemporal laser surveys, whether single spectral, multi-spectral of single-photon (White et al 2016;Yu et al 2017;Wästlund et al 2018).…”
Section: Forest Productivitymentioning
confidence: 99%
“…Wästlund et al [21] also found that single-photon LiDAR beams penetrate better through the canopy in hemiboreal forests than linear-mode LiDAR beams. Wästlund et al [21] used the Leica SPL100 instrument, whereas Swatantran et al [17] applied an experimental airborne single-photon LiDAR known as the High-Resolution Quantum LiDAR System. Mandlburger et al [23] reported that linear-mode LiDAR data can better characterize the vegetation below the dominant canopy surface than Leica SPL100 data.…”
mentioning
confidence: 98%
“…They observed that single-photon and linear-mode LiDAR data are able to characterize the canopy surface similarly, but that the pulses of linear-mode LiDAR penetrate deeper inside the canopy. Wästlund et al [21] and Yu et al [22] studied the estimation of forest variables using the Leica SPL100 and found that selected forest attributes can be predicted with comparable error rates with both linear-mode LiDAR and single-photon LiDAR data. Wästlund et al [21] also found that single-photon LiDAR beams penetrate better through the canopy in hemiboreal forests than linear-mode LiDAR beams.…”
mentioning
confidence: 99%
See 1 more Smart Citation